Development and characterisation of highly antibiotic resistant Bartonella bacilliformis mutants - Gomes, C (2016)
The objective was to develop and characterise in vitro Bartonella bacilliformis antibiotic resistant mutants. Three B. bacilliformis strains were plated 35 or 40 times with azithromycin, chloramphenicol, ciprofloxacin or rifampicin discs. Resistance-stability was assessed performing 5 serial passages without antibiotic pressure.